Blending the Focused Ethnographic Method and Case Study Research: Implications Regarding Case Selection and Generalization of Results. Issue 1 (February 2021) - Verd, Joan Miquel; Barranco, Oriol; Lozares, Carlos
In this article, we present the benefits of blending the methodological characteristics of the focused ethnographic method (FEM) and case study research (CSR) for a study on auxiliary work processes in a hospital in Barcelona, Spain. We argue that incorporating CSR logic and principles in the FEM produces a better form of inquiry, as this combination improves the quality of data and the ability to make comparisons in addition to enhancing the transferability of findings. These better outcomes are achieved because the characteristics of the case study methodological design reinforce many of the strengths of the FEM, such as its thematic concreteness and its targeted data collection. The role played by the theoretical framework of the study thus makes it easier to focus on the key variables of the initial theoretical model and to introduce a logic of multiple case comparison.